Description of loads in an annual training cycle of young football players - Wieczorek, A.; Sliwowski, R. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2004)
The problem of training loads is still an area open for scientifi c penetration having direct practical implications. At the present stage of knowledge about training loads it becomes possible to rationally distribute training measures to adjust them to the adequate level of a sports group and the specifi city of a given sport, as well as to modify the size of loads in consecutive stages of training so that they have a stimulating quality. This should lead to the development of model values of training loads in various sports. The problem of loading in sports games is more diffi cult to solve than in individual sport, since the performance of a team is the combined eff ort of many individuals. The aim of this study is to carry out a qualitative and quantitative analysis of training loads eff ected in an annual training cycle of young football players. The study was carried out among a group of 24 football players of Wielkopolski klub Pilkarski "Lech" (Wielkopolska Football Club) aged 14-15. Training loads were registered according to the methodology proposed by Sozanski and co-authors, taking into account the identifi catin of eff orts in terms of type of performed exercises and their intensity. The process of training of the analysed team is characterised by the prevalence of special measures carried out in the third scope of intensity with some use of directed measures. The structure of training loads of the Lech Poznan under-15s in an annual training cycle (40 % - comprehensive and directed loads and 60 % special loads) is a proposition for a model solution to the problem of training loads in a group of young football players.